Pengembangan Co-Production: Sebagai Upaya Meningkatkan Partisipasi Masyarakat Dalam Peningkatan Pelayanan Publik (Best Practice Pada Pelayanan Publik Di Kota Bandung) - Safitri, Yudiantarti; Andari, Rosita Novi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2015)
The co-production concept is becoming a new trend in the UK to make improvements in public services with innovative way. Loeffler pointed out that co-production in public services means professionals and citizens making better use of each other’s assets, resources and contributions to achieve better outcomes and improved efficiency (it takes two—professionals and communities). There are four types of co-production; co-commissioning, co-assessment, codesigning, and co-delivery. By using these types of co-production, public services can be developed and it involves public participation in the process. Bandung is one of the cities that have various types of programs, with these programs government tries to involve communities to work together with the government to improve public services. However, thereare some weaknesses in some programs thus making the programs’ implementation inefficient. (Needham, 2007) By using the coproduction concept, these programs can be developed to achieve maximum results. In the end, all cities in Indonesia can use the co-production concept to improve public services in their cities. All that is needed is for each city’s mayor to implement the co-production concept.